On the law reforms which have been successfully advocated by the Trades Union Congress, and the further law reforms which they now seek - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1881)
When I learned that the Trades Union Congress, which has held twelve annual meetings, had fixed its next meeting to be held in Dublin, in September?thus visiting Ireland for the first time, I made some inquiries as to their proceedings and publications. One of the most recent of these is a letter from the Parliamentary Committee of the Congress, to the late Home Secretary, referring with satisfaction to the action of Parliament in passing the Summary Jurisdiction Act of 1879 for England and Wales. The Committee refer to this measure as of immense value in improving the administration of justice, and in securing the liberty of Englishmen.
Read before the Society, 25 May 1880
Keywords: Trade unions; Labour law; Law reform; Labour conditions; 314.15